Short Communication: Community knowledge and uses of sambiloto (Andrographis paniculata) in an Urban Herbal Village, Surabaya, East Java, Indonesia - RASYIDAH ULFA; FATMAH FATMAH; SUYUD WARNO UTOMO (Society for Indonesian Biodiversity, 2025)
Abstract. Ulfa R, Fatmah, Utomo SW. 2025. Short Communication: Community knowledge and uses of sambiloto (Andrographis paniculata) in an Urban Herbal Village, Surabaya, East Java, Indonesia. Biodiversitas 26: 4017-4022. Andrographis paniculata, commonly known as sambiloto or the bitter, is a widely recognized medicinal plant used traditionally across Asia. Known for its bitter taste and pharmacological benefits, this plant is commonly used to treat fever, influenza, inflammation, diabetes, and infections. Despite its broad health applications, the level of public knowledge and actual utilization of A. paniculata in urban areas remains understudied. This study examined the correlation between community knowledge and practical uses of A. paniculata in Kampung Herbal Nginden, an urban herbal village in Surabaya, East Java, Indonesia. A mixed-methods approach was used, including structured questionnaires with 105 respondents and in-depth interviews with key community informants. The results showed that 52% of respondents demonstrated high knowledge of A. paniculata, yet only 44% actively utilized the plant in their daily life. A significant correlation was found between knowledge and utilization (p: 0.001), with high-knowledge individuals being 7.58 times more likely to use the plant. These findings highlight the need for increased community awareness and educational interventions, which are crucial for supporting the sustainable use of medicinal plants in urban settings. Community-based approaches, such as Kampung Herbal Nginden, provide a valuable foundation for preserving urban ethnobotanical practices, where cultural practices are often challenged by modernization and pharmaceutical dominance. Promoting ethnobotanical knowledge and practical use in urban environments is essential not only for public health but also for conserving cultural heritage and medicinal plant biodiversity.